A 'futures' approach towards the wellbeing of future generations in Wales and beyond. (30th September 2020) - Azam, S
Abstract: 'Futures' is a way of thinking about future uncertainty. It is not about predicting the future but is about developing alternative futures or scenarios and using them to inform how best to move towards the preferred future. This approach has been explored and applied to Wales, the UK, which has the Well-being of Future Generations (Wales) Act 2015. This Act has been globally recognised as a unique sustainable development legislation, putting Wales at the forefront of creating a different future for generations to come. Whilst most public bodies have always had responsibilities in delivering a range of services to support health and wellbeing, one of the key innovative requirements of the Act is the focus on the 'future', which by definition requires new and different approaches. This in turn means new tools, new skills and a new and different mind-set in which planners, commissioners, policy makers and service providers need to take a long-term view to addressing health and well-being. The presentation will explore the various approaches, methods and tools for 'futures' thinking and how this innovative agenda is progressing in Wales.